2016
DOI: 10.1038/bmt.2016.156
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of allogeneic stem cell transplantation for AML and myelodysplastic syndrome in elderly patients (⩾60 years)

Abstract: Allogeneic stem cell transplantation (SCT) remains the best curative option for patients with refractory AML or with high-risk myelodysplastic syndrome (MDS). For decades, age alone had been widely used as the primary criterion to assess eligibility for allogeneic SCT; however, prospective studies to evaluate allogeneic SCT in elderly patients are still limited. A total of 187 patients (median age of 64 years, range 60-77 years) with AML (87%) or MDS (13%) transplanted between 1999 and 2014 were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 31 publications
6
14
0
Order By: Relevance
“…Data showed a disease-free survival approaching 50% at 1 year in elderly patients with AML or MDS under RIC with Fludarabine, BCNU and Melphalan (FBM) [5][6][7][8]. Pohlen et al published retrospective data on AML/MDS patients above 60 years that showed excellent survival data in line with previously published reports [9]. Due to the promising results of large retrospective studies on a rapidly growing patient cohort >70 years that has been successfully transplanted since 2000 [10,11], alloHCT has been increasingly understood as feasible and effective.…”
Section: Introductionsupporting
confidence: 59%
“…Data showed a disease-free survival approaching 50% at 1 year in elderly patients with AML or MDS under RIC with Fludarabine, BCNU and Melphalan (FBM) [5][6][7][8]. Pohlen et al published retrospective data on AML/MDS patients above 60 years that showed excellent survival data in line with previously published reports [9]. Due to the promising results of large retrospective studies on a rapidly growing patient cohort >70 years that has been successfully transplanted since 2000 [10,11], alloHCT has been increasingly understood as feasible and effective.…”
Section: Introductionsupporting
confidence: 59%
“…Similar to our observation, a recent study by Pohlen et al showed 3 year OS of 43-54% for LR/IR DRI and 18-32% for HR/VHR DRI in 187 elderly patients (≥ 60 years) with AML or MDS. [8] Our study broadens Pohlen's findings to a larger range of hematologic malignancies and includes umbilical cord donor source for elderly patients, a population not included in their analysis. Although our study did not include large enough numbers of each DRI subgroup to make generalizations, particularly in high-risk and very-high risk DRI subgroups, our findings are consistent with a large CIBMTR registry report showing 2-year OS rates ranging from 64% for LR DRI group to 24% for VHR DRI group in adults of all ages with hematologic malignancies.…”
Section: Discussionmentioning
confidence: 97%
“…[4] [5] Several studies have shown that elderly patients ≥ 60 years of age have similar treatment-related mortality (TRM) and overall survival (OS) post-alloHCT compared to younger patients, with the majority of transplants utilizing reduced-intensity conditioning (RIC) regimens. [6][7][8][9]…”
Section: Introductionmentioning
confidence: 99%
“…For long‐term remission in fit older patients, allo‐SCT remains the most effective post‐remission strategy, with 38% 2‐year overall survival (OS) in CR1 for patients older than 69 years and a 3‐year OS of 49% for patients older than 60 years 10,11 …”
Section: Case 1: Is There Still a Role For Intensive Chemotherapy Formentioning
confidence: 99%